Migration, reterritorialization, and infrastructure: The Formation of the Urban Territory of Mato Grosso under the Logic of Agribusiness - Ravache, Rosana Lia; Godoy, Jeane Aparecida Rombi de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2025)
Objective – critically analyze the process of territorial and urban formation of Mato Grosso, based on the migration of settlers known as “paus rodados” and the implementation of public policies guided by the logic of agribusiness and logistical infrastructure. Methodology – The methodology adopts a qualitative approach, based on bibliographic review, historical analysis and critical territorial reading. Originality/Relevance – The research highlights the contradictions of the current model, such as land concentration, urban fragmentation, territorial selectivity and environmental degradation, problematizing their effects on spatial justice and the right to the city. Results – The cities resulting from the process of reterritorialization and urbanization practiced in Mato Grosso demonstrate a model of territorial development that intensely articulates technique, capital and state policy, characteristics that reveal an urban configuration characterized by fragmentation, functional sectorization and socio-spatial inequality, compromising its capacity to provide quality of life, inclusion and well-being. Theoretical/Methodological Contributions – By focusing on medium-sized cities that emerged along highways such as BR-163, the study investigates how technically planned productive expansion reconfigured urban-regional space, promoting a functionalized, socially exclusive, and environmentally unsustainable urbanization. Social and Environmental Contributions – The article contributes to urban and regional studies by proposing the overcoming of technocratic paradigms through a territorial rationality anchored in equity, diversity and sustainability.